Critical-Analytical History Learning: Alternative Learning Strategies Based on Geap Learning (Giving, Exploration, Analyze, Project) - Rista, Linggar Charista Shary; Widiadi, Aditya Nugroho; Hudiyanto, R. Reza (Yupa: Historical Studies Journal, 2024)
The development of the times and technology has a great influence on the implementation of educational practices. This also has an impact on the world of education, one of the things that can be done to take advantage of these technological developments is to develop learning strategies. The problem of learning history which is often considered boring and memorized learning can be overcome through various things. One of the offers of innovation in learning history is to develop learning strategies by integrating technology in it and training students' ability to analyze and think critically to create meaningful experiences for students through independent knowledge building so that learning history does not only have the impression of being rote learning. The purpose of this research is to develop a new concept of history learning strategy as an alternative to critical-analytical learning. The method used in this research is the research and development method or R&D, design instruction. Based on this research and development, it produces a geap learning history learning strategy (giving, exploration, analyze, and project) that can be implemented during history learning activities.